Foldable glycoprobes capable of fluorogenic crosslinking of biomacromolecules. Issue 10 (19th July 2016) - Li, Kai-Bin; Li, Na; Zang, Yi; Chen, Guo-Rong; Li, Jia; James, Tony D.; He, Xiao-Peng; Tian, He
Abstract : We demonstrate a foldable, fluorogenic glycoprobe that can recognize and simultaneously crosslink a receptor protein to form unique supramolecular bio-ensembles. Abstract : Small-molecular probes capable of monitoring and interfering with the activity of biomacromolecules – such as polysaccharides, nucleotides and proteins – are of paramount importance to the advancement of life science. However, such probes that can detect and simultaneously modulate the construction of biomacromolecules are elusive. Here we report a fluorogenic, foldable glycoprobe that can recognize and assemble a protein receptor in a synchronous fashion. The glycoprobe synthesized by introducing a glycoligand (for protein recognition) to a bola-type bis-fluorophore conjugate shows a "self-shielded" fluorescence in the folded state. Association with a receptor protein rapidly unfolds the probe, releasing a fluorophore capable of crosslinking the proteins – as determined using small-angle X-ray scattering – thereby producing a unique fluorescent supramolecular construct. We have demonstrated the use of the foldable glycoprobe in order to track the endocytic cycle of a transmembrane receptor.